1987
DOI: 10.1258/002367787781363444
|View full text |Cite
|
Sign up to set email alerts
|

Does the rat have an empty stomach after an overnight fast?

Abstract: Variable amounts of food have been observed in the stomachs of male rats following an overnight fast. The effects of diet and diet type on the amount of residual food left in the stomach and on fat deposition and liver weight in the male rat were investigated. The implications of these results on metabolism and pharmacokinetic studies are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…A limiting ridge, a thickened portion of lamina propria, separates these portions (Kararli, 1995;DeSesso and Jacobson, 2001). This limiting ridge and dual-portioned stomach may account for why food is present in the rat stomach after a 12-hour fast, whereas the human stomach is over 90% empty after only 4 hours of fasting (Read et al, 1986;Jeffrey et al, 1987). Also, the duodenum, jejunum, and ileum make up 4%, 38%, and 58% of the small intestine, respectively, in humans and 8%, 90%, and 2% of the small intestine in rats.…”
Section: Discussionmentioning
confidence: 99%
“…A limiting ridge, a thickened portion of lamina propria, separates these portions (Kararli, 1995;DeSesso and Jacobson, 2001). This limiting ridge and dual-portioned stomach may account for why food is present in the rat stomach after a 12-hour fast, whereas the human stomach is over 90% empty after only 4 hours of fasting (Read et al, 1986;Jeffrey et al, 1987). Also, the duodenum, jejunum, and ileum make up 4%, 38%, and 58% of the small intestine, respectively, in humans and 8%, 90%, and 2% of the small intestine in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of this fact, it must be known how long the animal can be starved without any harm to its welfare. For instance, Jeffrey et al (1987) observed variable amounts of food in the stomachs of male rats following an overnight fast and noted that the diet type and diet regimen can result in variable quantities of food being retained in the stomach after fasting overnight. However, Schlingmann et al (1997) found that the stomach of rats fasting 6, 12 and 18 hours was almost empty and that only rats fasted for 6 hours did not show any distress.…”
Section: Oral Administration (Per Os}mentioning
confidence: 99%